Evaluation of the use of prenatal immune stimulation to alter postnatal immune function in weaned pigs - Burdick Sanchez, Nicole C.; Mitchell, Ty; Broadway, Paul R.; Bowen, Brooke M.; Davis, Emily M.; Dobbins, Thomas; Barker, Samantha N.; Legako, Jerrad F.; Petry, Amy L.; Carroll, Jeffery A. (Frontiers in Animal Science, 2024)
This study was designed to determine whether exposure to low dose endotoxin (lipopolysaccharide; LPS) during gestation can enhance immunity to a subsequent LPS challenge in piglets after weaning. Pregnant sows (parity: 2.6 ± 1.4) were assigned to prenatal immune stimulation (PIS; n = 7; administered 2.5 µg/kg BW LPS i.m.) or saline treatment groups (CON; n = 7) administered at d 78 ± 1.8 of gestation. From the 2 prenatal treatment groups, barrows (n = 17 PIS, 17 CON) were identified at weaning (21 ± 1.3 d of age) to subsequently receive a post-weaning LPS challenge. On d -1, pigs were fitted with indwelling jugular catheters and subcutaneous temperature loggers. On d 0, pigs were challenged i.v. with LPS (10 µg/kg BW), and blood samples were collected at -2, 0, 1, 2, 4, 6, 8, 12, and 24 h relative to LPS challenge. There was a treatment × time interaction for subcutaneous temperature (P < 0.01), where temperature increased more quickly at 1 and 2 h post-challenge in PIS compared to CON pigs. There was a tendency (P = 0.08) for less change in white blood cells, relative to baseline values, in PIS compared to CON pigs. There was a treatment × time interaction (P = 0.01) for lymphocyte concentrations where concentrations were reduced in PIS compared to CON pigs at 8 h post-challenge. There was also a treatment × time interaction (P = 0.01) for the change in eosinophil concentrations, where there was less change in eosinophil concentrations from 1 to 12 h in PIS compared to CON pigs. There was a tendency (P ≤ 0.06) for a treatment × time interaction for serum interleukin-6 (IL-6) and IL-8. Granulocyte-macrophage colony-stimulating factor tended to be greater, and tumor necrosis factor-α tended to be reduced in PIS compared to CON pigs (P ≤ 0.08). These data suggest that exposure to endotoxin in utero may influence the postnatal innate immune response to endotoxin. More research is necessary to further understand the mechanism behind the differences observed and the potential long-term influence of prenatal immune stimulation on pig offspring.